PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK MELALUI CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN BARANG DAN KONSUMSI TERBUKA (TBK) TAHUN 2019-2021 - Posumah, Garfild Fredrik Oliver (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This study aims to determine the effect of leverage and profitability on tax avoidance through corporate social responsibility. The type of research used is quantitative research. The population used in this study are goods and consumption companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The sampling technique used in this study was purposive sampling. The data used in this study are secondary data obtained from the Indonesian Stock Exchange database and consumer and goods company websites. Methods of data collection using documentation that is based on the company's financial statements. The data analysis technique of this research uses SEM-PLS. The results of this study indicate that leverage and profitability have no effect on corporate social responsibility. Meanwhile, leverage and CSR have no effect on tax evasion. Profitability affects tax avoidance. Meanwhile, CSR is not able to mediate the effect of leverage and profitability on tax evasion.